Energy, exergy and economic analysis of biomass and geothermal energy based CCHP system integrated with compressed air energy storage (CAES). (1st November 2019) - Zhang, Xiaofeng; Zeng, Rong; Deng, Qiaolin; Gu, Xiaosong; Liu, Huaican; He, Yecong; Mu, Kang; Liu, Xiaobo; Tian, Hong; Li, Hongqiang
Highlights: A biomass and geothermal based CCHP system combined with CAES is proposed. Energy, exergy and economic analysis of proposed system are performed. Effects of key operating parameters on system thermodynamic performance are studied. The round trip efficiency and exergy efficiency are 90.06% and 31.52%, respectively. Variations of dynamic payback period under fuel and products costs are investigated. Abstract: In this research, a novel combined cooling, heating and power (CCHP) system taking biomass and geothermal energy as co-feeds is proposed, which is mainly consist of four subsections: biomass gasification, compressed air energy storage (CAES), bio-gas turbine power generation and ground source heat pump (GSHP). The compressed air energy storage absorbs off-peak electricity from grid and the high pressure air is utilized to combusted with bio-gas derived from biomass gasification process, the waste heat is utilized by absorption chiller and ground source heat pump. Energy, exergy and economic performances of proposed system are investigated. In the simulation condition, the round trip efficiency and exergy efficiency are 90.06% and 31.52%, respectively; the total investment cost of system equipment is 908008 and dynamic payback period can be reached at 3.032 year. In the parametric analysis, the effects of key parameters on system performances have been investigated. The system can be reached at an optimum performance when equivalence ratio is 0.275. The energy and exergy efficiency all improve with the increase in air outlet temperature of HX-01, while these criteria shows different tendency with the variations of inlet temperature of gas turbine, inlet and outlet pressure of air storage cavern. Moreover, the dynamic payback period of proposed system increases with the increase in off-peak electricity and biomass cost, whereas decreases with the increase in on-peak electricity cost, hot water cost and cooling cost. The proposed system provides a new way for renewable energy based integration system.